The Impact of Physical Activity on Neuroprotection in Neurodegenerative Diseases: A Special Focus on Parkinson’s Disease - Aleksandra Buczek; Paulina Jakubczyk; Olga Bilczewska; Wiktoria Janik; Marta Handschuh; Justyna Helis; Piotr Widera; Aleksandra Banaś; Maciej Michalik; Hubert Bigajski (Quality in Sport)
Aim of the study This study examines the impact of physical activity on neuroprotection in neurodegenerative diseases, focusing on Parkinson’s Disease (PD). It evaluates neuroprotective mechanisms, analyzes physical activity’s role in PD progression, assesses various exercise forms’ effectiveness on PD symptoms, and identifies research challenges and future directions.